2006
DOI: 10.1016/j.brainres.2006.09.089
|View full text |Cite
|
Sign up to set email alerts
|

Myelination and nodal formation of regenerated peripheral nerve fibers following transplantation of acutely prepared olfactory ensheathing cells

Abstract: Transplantation of olfactory ensheathing cells (OECs) into injured spinal cord results in improved functional outcome. Mechanisms suggested to account for this functional improvement include axonal regeneration, remyelination and neuroprotection. OECs transplanted into transected peripheral nerve have been shown to modify peripheral axonal regeneration and functional outcome. However, little is known of the detailed integration of OECs at the transplantation site in peripheral nerve. To address this issue cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 34 publications
1
52
0
2
Order By: Relevance
“…OECs, which guide the continuously regenerating axons of the olfactory neuroepithelium towards the olfactory bulb, have shown to retain a higher migratory potential and ability to penetrate glial scars in comparison to SCs (Franklin and Barnett, 1997), a property which makes them a rational trans-plantation candidate for nerve reconstruction. The employment of OEC transplantation in injured peripheral nerves have shown that, in rodents, these cells can provide trophic support, form cel-lular bridges across the site of injury, and significantly promote axonal regeneration (Verdú et al, 1999;Guntinas-Lichius et al, 2001;Radtke et al, 2005Radtke et al, , 2010Dombrowski et al, 2006).…”
Section: Tissue Engineering Of Peripheral Nervesmentioning
confidence: 99%
See 1 more Smart Citation
“…OECs, which guide the continuously regenerating axons of the olfactory neuroepithelium towards the olfactory bulb, have shown to retain a higher migratory potential and ability to penetrate glial scars in comparison to SCs (Franklin and Barnett, 1997), a property which makes them a rational trans-plantation candidate for nerve reconstruction. The employment of OEC transplantation in injured peripheral nerves have shown that, in rodents, these cells can provide trophic support, form cel-lular bridges across the site of injury, and significantly promote axonal regeneration (Verdú et al, 1999;Guntinas-Lichius et al, 2001;Radtke et al, 2005Radtke et al, , 2010Dombrowski et al, 2006).…”
Section: Tissue Engineering Of Peripheral Nervesmentioning
confidence: 99%
“…Transplantation of OECs (Radtke et al, 2005;Dombrowski et al, 2006) into the regenerating sciatic nerve of rodents showed that OECs survived, distributed longitudinally across the lesion site and were integrated into the repaired nerves, contributing to the myelin formation of regenerated axons. These authors hypothe-sized that, after lesion, transplanted OECs are primed to produce neurotrophins and, therefore, can have an immediate effect on the injured axons before scar formation occurs.…”
Section: Tissue Engineering Of Peripheral Nervesmentioning
confidence: 99%
“…Choi and Raisman demonstrated that the rate of eye closure increased after OEC transplantation in a facial nerve lesion model but that aberrant nerve branching was unchanged [75]. Schwann cells [76] and OECs [77] transplanted into transected sciatic nerve integrate into the injury site and form peripheral myelin on the regenerated axons. Moreover, the nodes of Ranvier of the regenerated axons myelinated by the transplanted cells express the appropriate sodium channel (Na v 1.6).…”
Section: Possible Contribution Of Olfactory Ensheathing Cell Transplamentioning
confidence: 99%
“…Moreover, the nodes of Ranvier of the regenerated axons myelinated by the transplanted cells express the appropriate sodium channel (Na v 1.6). Whether these engrafted cells accelerate or improve functional outcome after nerve injury is yet to be determined [77].…”
Section: Possible Contribution Of Olfactory Ensheathing Cell Transplamentioning
confidence: 99%
“…Some preclinical studies report that transplantation of olfactory ensheathing cells (OECs) for peripheral nerve injury in acute phase enhanced peripheral nerve restoration. [5][6][7][8][9] Currently, there are no reports about clinical studies on OEC for restoring chronic peripheral nerve injury. Herein, we report the case of one patient with chronic sciatic nerve injury who received OEC therapy and showed neurological functional improvement.…”
Section: Introductionmentioning
confidence: 99%